Study of Saline Infusion Sonography and Hysterosalpingography to See the Tubal Patency in the Infertile Women - Akter, Jesmin; Rahman, Fatema (Journal of Comilla Medical College Teachers' Association, 2023)
Background: Infertility is a global issue in reproductive health. Etiology Of infertility is multifactorial and fallopian tube abnormality being one of the most important causes accounts for up to 40%of female infertility. Saline infusion sonography (SIS) is gaining popularity and being widely practiced and accepted as a screening tool in assessing tubal patency. Objectives: To compare the efficacy of tubal patency test with saline infusion sonography and hysterosalpingography in infertile women. Methods: It is a quasi-experimental study. 120 consecutive infertile women in 25-40 years, who are ovulating spontaneously or by ovulation induction who was needed tubal assessment included here. 60 patients went for saline infusion sonography, 60 went for hysterosalphingography which was allocated by lottery. Result: Main outcome was find out the diagnostic accuracy of saline infusion sonography over conventional hysterosalpingography for evaluation of tubal patency. Tubal patency confirmed by SIS 54(89.99%) had at least one tube patent. Tubal block 6(10.01%). HSG bilateral tubal patency 40(66.67%), bilateral tubal block 15(25.00%), unilateral block 5(8.33%). SIS had sensitivity 86% specificity 97%, positive predictive value 97% and negative predictive value 83% in tubal patency. Conclusion: SIS employed as a screening procedure to pick up subjects needing HSG and laparoscopy Low risk subjects for tubal factors in infertility, sonohysterosulphingography can be. It is simple, relatively less expensive, minimally invasive procedure. J Com Med Col Teachers Asso Jan 2023; 27(1): 27-33